2002
DOI: 10.1152/ajpregu.00056.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fetal ovine adrenalectomy on sympathetic and baroreflex responses at birth

Abstract: Studies were performed to test the hypothesis that the absence of adrenal glucocorticoids late in gestation alters sympathetic and baroreflex responses before and immediately after birth. Fetal sheep at 130–131 days gestation (term 145 days) were subjected to bilateral adrenalectomy before the normal prepartum increase in plasma cortisol levels. One group of fetuses ( n = 5) received physiological cortisol replacement with a continuous infusion of hydrocortisone (2 mg · day−1 · kg−1 for 10 days), whereas the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Previous studies from this and other laboratories have demonstrated that systemic glucocorticoid administration can increase the arterial pressure midpoint and decrease the gain of baroreflex control of heart rate and renal sympathetic nerve activity (37,40,(42)(43)(44). However, the sites of action of Cort to modulate baroreflex function have not been determined.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies from this and other laboratories have demonstrated that systemic glucocorticoid administration can increase the arterial pressure midpoint and decrease the gain of baroreflex control of heart rate and renal sympathetic nerve activity (37,40,(42)(43)(44). However, the sites of action of Cort to modulate baroreflex function have not been determined.…”
Section: Discussionmentioning
confidence: 91%
“…Many of these risk factors are also associated with dysregulation of autonomic function (2, 14, 36). However, the mechanisms by which glucocorticoids modulate arterial pressure regulation, particularly with respect to the effects of glucocorticoids on central pathways controlling autonomic function, remain poorly understood.Studies in animals indicate that systemic elevations in glucocorticoids can modulate the function of the arterial baroreceptor reflex (12,37,40,(42)(43)(44). The arterial baroreceptor reflex is an autonomic reflex that is important for the shortterm, and possibly long-term, regulation of arterial pressure (3,29,32,50).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is not known whether insulin secretion was altered in the present study. It is possible that betamethasone treatment prematurely developed sympathetic suppression of insulin secretion, since previous studies have shown that glucocorticoids have a maturational effect on the sympathetic response at birth (Segar et al 1998(Segar et al , 2001(Segar et al , 2002. We have previously shown, however, that offspring treated with prenatal glucocorticoids exhibit exaggerated insulin responses to a glucose bolus at 1 year of postnatal age, rather than inhibited insulin secretion (Moss et al 2001).…”
Section: Discussionmentioning
confidence: 93%
“…In general, stressors can elicit responses from both the SAM and hypothalamic pituitary adrenal (HPA) axes. Animal studies also have demonstrated that ACTH and glucocorticoids contribute to cardiovascular regulation through modulation of the baroreceptor sensitivity and sympathetic activity (26,27). Effects for the HPA axis are usually quantified by differences in subjects' salivary cortisol levels before and after exposure to stressors.…”
Section: Discussionmentioning
confidence: 99%